A study of deranged liver function as an early predictor of perforated appendix - B. B., Ananda; M. N., Madhusudana; R., Santhosh (International Surgery Journal, 2018)
Introduction: Appendicectomy accounts for 1% of all surgical operations. Portal blood carries nutrients and substances absorbed from gut including bacteria. It is commonly cleared by detoxification and immunological action of reticuloendothelial system. When bacterial load overwhelms the Kupffer cell function, causes dysfunction or damage to the hepatocytes. It reflects, rise in serum bilirubin alone or in combination with liver enzymes depending upon the type, severity and site of lesion. Recently, another substance known as cytokines have also been labelled to be responsible for depressed excretory function of liver. To study deranged liver function test as a predictor of perforated appendix. Methodology: This is a prospective study conducted at Dr. BR Ambedkar Medical college and Hospital between 2015-2017. Clinically suspected cases are investigated to confirm the diagnosis. Subsequently these cases are operated and clinical diagnosis was confirmed pre-operatively and post-operatively by histopathological examination of the specimen. Their clinical and investigative data are compiled and analysed and following observations are obtained. Routine liver function test results are compared with laboratory reference values. Results: In present study non-perforated cases mean total bilirubin was 1.25 and in perforated group 1.83. SGOT in non-perforated cases was 44.58IU/L and perforated cases 107.33IU/L. SGPT in non-perforated cases was 52.19IU/L and perforated cases was 113.33IU/L. Hyperbilirubinemia in perforated appendicitis vs simple appendicitis had a specificity of 75% for perforated appendicitis, a sensitivity of 100%. Conclusions: Elevated serum bilirubin has a high potential in predicting perforation of appendix in clinically suspected cases.